New Strategies for Innovative and Enhanced Meat and Meat Products - Delgado-Pando, Gonzalo; Pintado, Tatiana (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Meat and meat products are an important part of the human diet. Even though non-essential, they provide high amounts of protein, vitamins, and minerals in a concentrated form. However, the consumption of meat and meat products has been associated with an increased risk of health-related problems. Once the harmful components of meat and meat products are elucidated, novel technologies can help in identifying, removing, replacing, and/or minimising their deleterious effects. In addition, meat products can be and are being utilised as carriers of added bioactive compounds due to their processing versatility and high worldwide consumption. New strategies in the field of meat and meat product development are certainly needed in order to overcome not only the health-related problems these products might contribute to, but also from the sustainability and economy perspective. This book compiles ten original studies and two comprehensive reviews that will tackle some of these issues.